2020
DOI: 10.1051/radiopro/2020025
|View full text |Cite
|
Sign up to set email alerts
|

Societal uncertainties recognised in recent nuclear and radiological emergencies

Abstract: The paper aims to stimulate reflection and debate on the issue of uncertainty as a key component of nuclear or radiological emergency management. It identifies and discusses different types of uncertainties that appeared during and after real emergencies. For this, seven different case studies of nuclear and radiological events have been analysed using three separate methodological approaches: i) case descriptions (document review); ii) media analysis; and iii) semi-structured interviews. The overall objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…A systematic review of social science studies in the field of radon showed that there is a lack of social science, in general, and of comparative studies to support radon communication campaigns, in particular; although the attitudes and behaviours of sub-populations could differ from those of the general public, they are mostly not investigated and addressed; the methods and scales used in surveys should be improved; there is a lack of accurate selection and description of sampling strategies, measurement tools, research protocols and data analysis procedures; ethical aspects are often overlooked [ 26 ].…”
Section: Some Gaps In Existing National Radon Control Strategiesmentioning
confidence: 99%
“…A systematic review of social science studies in the field of radon showed that there is a lack of social science, in general, and of comparative studies to support radon communication campaigns, in particular; although the attitudes and behaviours of sub-populations could differ from those of the general public, they are mostly not investigated and addressed; the methods and scales used in surveys should be improved; there is a lack of accurate selection and description of sampling strategies, measurement tools, research protocols and data analysis procedures; ethical aspects are often overlooked [ 26 ].…”
Section: Some Gaps In Existing National Radon Control Strategiesmentioning
confidence: 99%
“…Social uncertainties in how expert recommendations are implemented in society may refer to public acceptance and compliance with protective actions advice; social and economic consequences of the recommendation and actions, and uncertainties in those consequences; and the level of stakeholder and public engagement used or planned (Turcanu et al, 2020b). Ethical uncertainties also refer to whether members of a population feel that they have control over or have given consent to being exposed to a particular level of risk and the need to be sensitive to inequalities in the distribution of risk (Oughton et al, 2004;Tomkiv et al, 2020). Again debate and deliberation, when possible with the engagement of affected stakeholders, are the only useful way forward (Nisbet et al, 2010).…”
Section: Value Social and Ethical Uncertaintiesmentioning
confidence: 99%
“…During nuclear emergencies, people experience high uncertainty [24]. Uncertainty occurs when a) details of situations are ambiguous, complex, unpredictable or probabilistic; b) information is unavailable or inconsistent; and c) people feel insecure in their own state of knowledge or the state of knowledge in general [46].…”
Section: H1: Public Information Needs Are Met By Responsible Nuclear ...mentioning
confidence: 99%
“…Not only the Fukushima Daichii accident but also recent nuclear and radiological emergencies indicate the need to update public communication plans and practices in Europe. Tomkiv et al [24] recognise that one of the most significant components of uncertainties in nuclear emergency management are contradictory information and communication aspects, technical and measurement uncertainties, societal impacts and The successive emergency events at the Tricastin nuclear site during the period July-September 2008 triggered a new initiative from the operator and the institute for radiation protection and nuclear safety (IRSN), under the supervision of the French nuclear safety authority, as they were urged to engage with stakeholders [27]. A pluralistic committee was established in order to allow different stakeholders involved in emergency and post-emergency management to discuss research results and respond to public concerns.…”
Section: Introductionmentioning
confidence: 99%